Transfection of unmodified oligodeoxynucleotide with polyethylenimine reduces the level of hepatitis B surface antigen - Lin, Junyu; Li, Jing (Frontiers in Microbiology, 2025)
IntroductionThe delivery of nucleic acid into cells using polyethylenimine (PEI) as non-viral carrier is a potential candidate technique for the treatment of hepatitis B virus (HBV) infection.MethodsIn the present study, PEI was used as cationic polymers and transfected with unmodified oligodeoxynucleotides in cell cultures and the BALB/c mouse model to investigate its efficiency in blocking HBV surface antigen (HBsAg) secretion.Results and discussionPEI/oligonucleotide complexes selectively inhibited HBsAg secretion in the culture supernatant, while there were no evident alterations in HBeAg and HBV DNA levels, thereby suggesting its potential inhibitory activity against the production of HBsAg. The complexes formed by PEI with double-stranded decoy oligonucleotides also suppressed HBsAg secretion but showed no expected interference with the intermediate levels of HBV transcription or replication. Furthermore, PEI/plasmid-DNA complexes demonstrated no influence on the expression levels of HBsAg, thus highlighting the specific effects of PEI/oligonucleotides exerted on HBsAg release. PEI-oligonucleotides transfection prior to the viral inoculation impaired HBV infection in HepG2-NCTP cells. Importantly, the PEI/oligonucleotide complex also induced the decline of HBsAg in hydrodynamically injected BALB/c mice. These findings demonstrate that transfection of PEI/oligonucleotide complexes can help effectively reduce HBsAg level and may offer a new potential avenue for the development of anti-HBV treatment.